STUDI KEPATUHAN KONSUMSI TABLET TAMBAH DARAH (TTD) DAN ASUPAN ZAT GIZI TERKAIT ANEMIA PADA SISWA PEREMPUAN DI SEKOLAH MENENGAH KEJURUAN (SMK) KOTA BEKASI, INDONESIA - Muh Nur Hasan Syah; Hana Novianti; Alfi Fairuz Asna; Silvia Mawarti Perdana (Media Gizi Mikro Indonesia, 2022)
Background. Anemia is a global nutrition problem, especially in developing countries. Several studied found that around 30 percent of the adolescent was anemia, especially in girls. Compliance with iron-folic acid (IFA) tablet consumption is the most influential factor in the successful improvement of iron status and combat anemia. Objective. This study aimed to know the relationship between compliance of IFA tablet consumption and anemi-related nutrient intake with the anemia among girl-students in Vocational High School in Bekasi City, Indonesia. Method. This study was a cross-sectional study conducted in five vocational high schools, with 345 samples. Samples were collected with a purposive sampling technique. Inclusive criteria for the sample are age between 12 and 18, healthy and able to be a subject, and excluded girls that were fasting and or menstruation. Hemoglobin (Hb) measured with the cyanmethemoglobin method, Hb under 12 g/dl was categorized as anemia. The compliance was assessed with a validated questionnaire and a validated food frequency questionnaire (FFQ) to measure and determine the nutrients intake. Data analyzed by univariate and bivariate. Results. The study found that 30.7 percent of girls were anemia and 48.1 percent as mild anemia (Hb 11–11.9 g/dl). From 74 percent who have not a compliant consumed IFA tablet, 34.3 percent was anemia. Most students have enough intake of protein and other macronutrients. In contrast, the study found more than 60 percent of students have less iron, vitamin C, and vitamin B12. There was no significant relationship among compliance IFA, energy intake, protein intake, fat intake, carbohydrates intake, iron intake, vitamin A intake, vitamin B12 intake, and vitamin C intake with the anemia (p>0.05). Conclusion. There was no relationship between compliance and nutrient intake with anemia. Nevertheless, nutrient intake can be related to anemia as well as compliance with iron tablet consumption. Research suggested that nutrition programs at school should be established, well monitoring, and evaluated.